SOSIALISASI PENCEGAHAN BULLYING DI LINGKUNGAN SEKOLAH - Dade Suparna; Imam Rosidi; Ani Sunarni; Yayah Nihayatul Husnai; Megarini Megarini; Atul Atul; Udin Suadma (Gapenas Publisher, 2023)
Basic education has a very important position, because it is the beginning of the formation of the pattern of a student. The development of the world of education is currently getting attention from all circles, especially educators, because of the rampant cases of bullying in schools. Bullying or bullying affects the psychological development and development of student character formation. This is homework for all of us so that in the future, students can avoid bullying. One of the efforts that can be done is by preventing bullying in the school environment. The method used in supporting bullying efforts in schools by using the stop bullying movement by providing socialization and good practices in the school environment, implementation techniques on a scheduled basis and continuously implemented. As a result, students understand the negative effects of bullying and understand how to prevent it